Prevalence and bacteriology of culture-positive urinary tract infection among pregnant women with suspected urinary tract infection at Mbarara regional referral hospital, South-Western Uganda - Bahati Johnson; Bawakanya Mayanja Stephen; Ngonzi Joseph; Owaraganise Asiphas; Kayondo Musa; Kabanda Taseera (BMC, 2021)
Abstract Background Urinary tract infections (UTIs) in pregnant women contribute about 25% of all infections and are among the most frequent clinical bacterial infections. Pregnancy changes in women that include anatomical, physiological and hormonal make them susceptible to develop UTI. Left untreated, UTI in pregnancy is associated with grave complications to the mother and fetus. These complications can be decreased by prompt and proper diagnosis and appropriate treatment that also reduces the emergency of drug resistance. Antimicrobial resistance is a major health problem in the treatment of UTI. We determined the prevalence, bacteriology and antimicrobial susceptibility of symptomatic urinary tract infection among pregnant women at Mbarara Regional Referral Hospital. Methods We conducted a cross-sectional study from November 2019 to February 2020 involving 400 pregnant women with symptomatic UTI. Patient information was obtained using a structured questionnaire. We collected clean-catch midstream urine specimens for culture and performed antimicrobial susceptibility testing following Clinical and Laboratory Standards Institute standards. Data was entered into RED-cap Version 8.2 software and then exported to Stata Version 14.1 for analysis. Results The proportion of culture-positive UTI was 140/400 (35%). Gram-negative bacteria were more prevalent (73%): Klebsiella pneumoniae 52(37.41%), Escherichia coli 40(28.78%), Pseudomonas aeruginosa and Proteus mirabilis 7(5.04% each), Citrobacter freundii 1(1%). Staphylococcus aureus 33(23.57%) was the only gram-positive isolate. All the isolates were resistant to ampicillin, amoxicillin, amoxicillin/clavulanic acid and ceftazidime/clavulanic acid (95.7, 95.0, 72.9 and 50.7% respectively). Prevalence of extended-spectrum beta-lactamases producing Enterobacteriaceae was 29.0% while that of methicillin-resistant Staphylococcus aureus was 33.3%. All cultures demonstrated resistance to more than one drug. Majority of the bacterial isolates were sensitive to ciprofloxacin, ceftriaxone, nitrofurantoin, cefotaxime and gentamicin at 82.9, 81.4, 79.3, 78.6, 66.4 and 65.7% respectively. Conclusions Klebsiella pneumoniae was the most prevalent isolate followed by E. coli. These two organisms were highly resistant to the commonly used antibiotics. Our study recorded a higher prevalence of culture-positive UTI in pregnancy than all the studies in Uganda. Empirical treatment of UTI should be minimized as sensitivity varies for each organism, for each drug and over time.